First principle study of structural, electronic, magnetic, optical and thermal properties of chalcogenides XFeSe2 (X = Li, Na and K) half metallic compounds. (1st December 2022) - Azam, A; Muhammad, Nawaz; Murtaza, G; Jafar, Naveed; Alshahrani, Thamraa; Amin, Mohammed A; Morsi, Manal; Somaily, H H; Mahmood, Q
Abstract: Half-metallic ferromagnets (HMF) are one of the most essential materials for spintronics and other energy applications. The electronic, magnetic, optical and transport properties of hexagonal XFeSe2 (X = Li, Na and K) compounds have been investigated by Wien2K code. The Heisenberg classical model is used to determine spin polarization. The ferromagnetism is calculated by the negative exchange energy Δ x (pd), exchange constants, and quantum exchange of electrons in strong p-d hybridization. The integer values of total magnetic moment ( M T ) 5.0000 μ B, 4.9995 μ B, and 5.0000 μ B per unit formula for LiFeSe2, NaFeSe2 and KFeSe2, respectively, have confirmed the HMF. Optical properties are revealed in terms of absorption of light energy in visible to ultraviolet regions, refractive index, reflectivity spectrum and optical conductivity. Lastly, BoltzTraP code was used to explore the influence of electrical and thermal conductivities of electrons spin, potential gradient effect and figure of merit (ZT). Results reveal that the studied compounds are potential candidates for spintronic devices and energy applications.